Ayat-Ayat Mutasyâbihât Perspektif Ibnu ‘Athiyyah - Yusron, Agus (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2020)
Ambiguity of meaning info a long debate of scholars form age to age, both from the theology and the commentators or scholars of the Koran. Ibn ‘Athiyyah, an exegete and includes experts in theology sect Maliki and Ash’ari in the field of theology. Tafsir Ibn ‘Athiyyah known as Al-Muharrâr al-Wajîz fi Al-Kitâb Al-Azîz is one tafseer that stands out with the language, so it is very detailed when there are verses in the Qur’an that are tasybih lafzhi or ma’nawi. This paper will present some of the verses of the Koran that mutashabihat particularly relevant paragraph anthropomorphism, so that we are better able to understand the meaning of these verses in view Ahlussunnah be represented by Ibn ‘Athiyyah. Mutashabihat verses there must be hundreds of them, but here only discussed about the meaning of the word al-istiwa’, al-wajh, al-‘ain, and al-yad. Which will be drawn from some of the verses of the Koran in various letters.